Cholesterol modification of proteins. - Mann, R.K.; Beachy, P.A. (Biochimica et Biophysica Acta, 2000)
The demonstration over 30 years ago that inhibitors of cholesterol biosynthesis disrupt animal development suggested an intriguing connection between fundamental cellular metabolic processes and the more global processes of embryonic tissue patterning. Adding a new dimension to this relationship is the more recent finding that the Hedgehog family of tissue patterning factors are covalently modified by cholesterol. Here we review the mechanism of the Hedgehog autoprocessing reaction that results in this modification, and compare this reaction to that undergone by other autoprocessing proteins. We also discuss the biological consequences of cholesterol modification, in particular the use of cholesterol as a molecular handle in the spatial deployment of the protein signal in developing tissues. Finally, the developmental consequences of chemical and genetic disruption of cholesterol homeostasis are summarized, along with the potential importance of cholesterol-rich lipid rafts in production of and response to the Hh signal.